2013
DOI: 10.1038/onc.2013.426
|View full text |Cite
|
Sign up to set email alerts
|

A functional interaction of E7 with B-Myb-MuvB complex promotes acute cooperative transcriptional activation of both S- and M-phase genes. (129 c)

Abstract: High-risk human papillomaviruses are causative agents of cervical cancer. Viral protein E7 is required to establish and maintain the pro-oncogenic phenotype in infected cells, but the molecular mechanisms by which E7 promotes carcinogenesis are only partially understood. Our transcriptome analyses in primary human fibroblasts transduced with the viral protein revealed that E7 activates a group of mitotic genes via the activator B-Myb-MuvB complex. We show that E7 interacts with the B-Myb, FoxM1 and LIN9 compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 45 publications
2
39
0
Order By: Relevance
“…B-Myb has been implicated in a positive regulatory role for Cdk1 expression (49,56). We and others have shown that E7 upregulates B-Myb expression (7,46). Moreover, downregulation of B-Myb-induced G 1 arrest in E7-expressing cells upon DNA damage has been described previously (59).…”
Section: Gene Expression Profiling Of Hpv-16 E7-expressing Cellsmentioning
confidence: 58%
See 3 more Smart Citations
“…B-Myb has been implicated in a positive regulatory role for Cdk1 expression (49,56). We and others have shown that E7 upregulates B-Myb expression (7,46). Moreover, downregulation of B-Myb-induced G 1 arrest in E7-expressing cells upon DNA damage has been described previously (59).…”
Section: Gene Expression Profiling Of Hpv-16 E7-expressing Cellsmentioning
confidence: 58%
“…Nonetheless, several gene expression profiling studies have been conducted on HPV E7-expressing cells using microarray analysis. The cells employed included mouse cells, cervical cancer cell lines (C33A and CaSki), and PHKs (3,(5)(6)(7)90). However, there are major limitations with the DNA microarray approach, such as the relatively high background noise resulting from solution-based DNA probe hybridization as well as the limited scope of profiling analysis, which is confined by the DNA probe set.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…E7 has been shown to enhance BUBR1 transcription by about 2.6 times when compared to GFP in primary fibroblasts using microarray experiments, 23 and accordingly to this result, the levels of BUBR1 were shown to be high in human foreskin fibroblasts stably expressing E7. 24 Interestingly, in synchronized HeLa cells released from G1/S transition for 6 hours (therefore around 4-6 hours before mitotic entry), the levels of BUBR1 were lower in cells expressing GFP-E2 and GFP-DTAD (which both repress E7) than in GFP-TAD and GFP-expressing cells (Fig.…”
Section: E6/e7 Expression and P53 Inactivation Potentiate E2 Effects mentioning
confidence: 72%